Vaca Muerta, mobility and the real estate market: an approach to the transformations of Añelo (2010-2022) (Huellas, 2024)
In the present work, we make an approach to the recent socio-spatial transformations of Añelo and its relationship with the international oil market. We propose to approach this phenomenon through the analysis of demographic, urban variations, and the real estate stock. First of all, we will briefly refer to the discovery of Vaca Muerta in the midst of the re-nationalization of YPF company and the re-primarization of Latin American economies. Secondly, we observe and characterize demographic changes and approach the oil labor market. Finally, we observe urban transformations exploring the process of spatialization of industrial activity and the distortion of markets mentioned previously. Methodologically, we propose an approach that combines quantitative and qualitative sources and constantly resorts to the game between the global, regional and local scales in an attempt to understand the effects of the transnational oil industry on the population and urban space of our case study.
Keywords: URBANIZATION; URBAN GROWTH; OIL